Lesepraktiken im antiken Judentum Rezeptionsakte, Materialität und Schriftgebrauch - Leipziger, Jonas (Materiale Textkulturen, 2021)
Practices of reading form an important center of synagogal worship as well as Jewish scholarship. The monograph reconstructs the development of ritual reading practices in ancient Judaism based on the triad of acts of reception, materiality, and scriptural use. In this context, Greek-speaking Judaism and its reception of the Greek Bible are given greater attention than before.